2009
DOI: 10.1002/crat.200900462
|View full text |Cite
|
Sign up to set email alerts
|

Structural, microchemical and superconducting properties of ultrathin NbN films on silicon

Abstract: Key words ultrathin NbN films, hot-electron bolometers, microstructure, transmission electron microscopy. PACS 68.37.Lp Structural, chemical and superconducting properties of thin NbN films used for development of fast and sensitive hot-electron bolometer (HEB) detectors for wide spectra range are reported. The thin NbN films with a thickness between 4 and 10 nm were deposited on the (001)Si substrates by magnetron sputtering. In order to investigate the film morphology and microchemistry, diffraction-contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
2
13
0
1
Order By: Relevance
“…(3) It is generally easier to be homogeneously disordered for a binary compound, like well-studied InO x and TiN films. Figure 1 shows that a nice superconductor-insulator transition is observed when the film thickness is reduced to a few unit cell 30 (one unit cell = 0.44nm). Superconducting and insulating films are separated by quantum resistance for cooper pairs, which is h/4e 2 = 6.45 kΩ.…”
Section: Methodsmentioning
confidence: 99%
“…(3) It is generally easier to be homogeneously disordered for a binary compound, like well-studied InO x and TiN films. Figure 1 shows that a nice superconductor-insulator transition is observed when the film thickness is reduced to a few unit cell 30 (one unit cell = 0.44nm). Superconducting and insulating films are separated by quantum resistance for cooper pairs, which is h/4e 2 = 6.45 kΩ.…”
Section: Methodsmentioning
confidence: 99%
“…If some parts of the strip are poorly protected by the resist etching via ion milling may decrease the thickness of the strip in those parts. The decrease of the thickness leads to suppression of superconductivity due to the intrinsic proximity effect [11,13]. Additional suppression initiated by the milling can be even larger than the suppression expected for the film of the same final thickness prepared directly by deposition.…”
Section: A Modelmentioning
confidence: 99%
“…It is well documented that the majority of the studies related to NbN are related to its superconducting properties [2][3][4]. Other excellent properties are high hardness and toughness compared to pure Nb, which makes it a suitable material for protective-wear coatings [5][6][7][8][9]. Kneisel et al, 2009 adopted the Conflat design with Nb and concluded that RF measurements on single-cell cavities indicated Nb-1Zr and NbN are good candidates for the flanges [5].…”
Section: Introductionmentioning
confidence: 98%
“…PLD is widely used for fabrication of many thin film materials such as hightemperature superconductors, semiconductors, and dielectrics [12]. Among these materials, niobium nitride films that have attracted considerable attention because of their excellent superconducting and mechanical properties [3,4,8,9,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%